Pipelined vedic multiplier with manifold adder complexity levels - Ansiya Eshack; S. Krishnakumar (Institute of Advanced Engineering and Science, 2020)
Recently, the increased use of portable devices, has driven the research world to design systems with low power-consumption and high throughput. Vedic multiplier provides least delay even in complex multiplications when compared to other conventional multipliers. In this paper, a 64-bit multiplier is created using the Urdhava Tiryakbhyam sutra in Vedic mathematics. The design of this 64-bit multiplier is implemented in five different ways with the pipelining concept applied at different stages of adder complexities. The different architectures show different delay and power consumption. It is noticed that as complexity of adders in the multipliers reduce, the systems show improved speed and least hardware utilization. The architecture designed using 2 x 2 – bit pipelined Vedic multiplier is, then, compared with existing Vedic multipliers and conventional multipliers and shows least delay.